Assessing the preparedness of the schooling system for The Fourth Industrial Revolution: The case study of two secondary schools in the Ekurhuleni South Education District - Haynes, Zena Gwyneth (Department of Social Development, 2023)
Research indicates that South African teachers do not understand the use of technology for teaching and learning, the benefits associated with it, and classrooms are not designed to support technology-integrated teaching (Skhephe, Caga and Boadzo, 2020). Furthermore, access to technology for education seems to be limited and unequal across the nine provinces and different school quintiles (Meyer and Gent, 2016 in Kayembe and Nel, 2019). Despite this, the World Economic Forum predicts that approximately 65% of children presently starting school will have jobs in the future that do not exist yet (Soler & Dadlani, 2020). These jobs will require specific skills and knowledge that are consistent with the rapid advances in technology. However, it is unclear if, and how the current South African schooling system is equipping learners with the skills required for future jobs. The purpose of this qualitative study was to assess the preparedness of schools for the Fourth Industrial Revolution (4IR) in the Ekurhuleni South Education District, in Gauteng Province. The study had four main objectives: to investigate how the 4IR is understood by teachers, learners and the Institutional Development and Support Official (IDSO) in the Ekurhuleni South Education District; to determine what the perceptions and experiences of teachers and the IDSO are on the preparedness of secondary schools in the Ekurhuleni South Education District for teaching in the 4IR; to find out what learners' experiences are of schooling in the 4IR; and to ascertain how learners perceive their schooling experiences to help them after school. This study employed a qualitative research approach to explore how the schools' preparedness for schooling in the 4IR is perceived and experienced by the participants. Twenty individual in-depth interviews were conducted with grade 12 learners. Additionally, seven key informant interviews were conducted with four secondary school teachers, two principals and one IDSO from the Ekurhuleni South Education District. Participants were selected through purposive and snowball sampling. Online interviews were conducted to adhere to COVID-19 health regulations. However, where learners did not have devices, in-person interviews were conducted. The findings revealed that grade 12 learners were not aware of the 4IR as a concept but had some knowledge of 4IR-related technologies including automation and robotics. Learners described their schooling experiences during 4IR as consisting of various personal and structural challenges. They reported on mostly using smartboards in the classroom but described several challenges with using the technology, such as issues related to power outages and lack of internet connectivity. Teachers described the 4IR in terms of fast and easy access to resources, people and information. They highlighted the advantage of using technology in terms of making lessons more interesting and interactive. Teachers also emphasised that the theft of devices and lack of training impacts on how effectively they use the technology. The principals reported that some teachers still showed resistance to using technology for teaching. They further reported that the schools did not offer any 4IR-related or basic information and communications technology (ICT) subjects and that current curricula was not aligned with the 4IR. The IDSO reported on the implementation of a twinning process of one of the schools, in an effort to facilitate the integration of ICT in the school. The IDSO also appraised the schools as not yet ready for teaching and learning of the 4IR. The lack of technology and other resources and infrastructure at the schools, lack of training and support for teachers, as well as the absence of 4IR subjects and curricula, reveal that the schools in this study are not prepared for schooling in the 4IR. Recommendations are made to the Gauteng Department of Education to offer better technology training and support to teachers. The schools and district office are encouraged to put measures in place to better protect devices and infrastructure from damage and theft. Recommendations for further research are also offered.